TickSialoFam (TSFam): A Database That Helps to Classify Tick Salivary Proteins, a Review on Tick Salivary Protein Function and Evolution, With Considerations on the Tick Sialome Switching Phenomenon - Ribeiro, José M. C.; Mans, Ben J. (Frontiers in Cellular and Infection Microbiology, 2020)
Tick saliva contains a complex mixture of peptides and non-peptides that counteract their hosts’ hemostasis, immunity and tissue-repair reactions. Recent transcriptomic studies have revealed over one thousand different transcripts coding for secreted polypeptides in a single tick species. These gene products belong to many expanded families such as the lipocalins, metalloproteases, Antigen-5, cystatins, apyrases, as well as families that are found exclusively in ticks, such as the evasins, Isac, DAP36 and many others. Phylogenetic analysis of the deduced protein sequences indicate that the salivary genes exhibit an increased rate of evolution due to a lower evolutionary constraint and/or positive selection, allowing for a large diversity of tick salivary proteins. Thus, for each new tick species that has its salivary transcriptome sequenced and assembled, a formidable task of annotation of these transcripts awaits. Currently, as of November 2019, there are over 287 thousand coding sequences deposited at the National Center for Biotechnology Information (NCBI) that are derived from tick salivary gland mRNA. Here, from these 287 thousand sequences we identified 45,264 potential secretory proteins which possess a signal peptide and no transmembrane domains on the mature peptide. By using the psiblast tools, position-specific matrices were constructed and assembled into the TickSialoFam (TSF) database. The TSF is a rpsblastable database that can help with the annotation of tick sialotranscriptomes. The TSA database identified 136 tick salivary secreted protein families, as well as 80 families of endosomal-related products, mostly having a protein modification function. As the number of sequences increases, and new annotation details become available, new releases of the TSF database may become available.